Letter to the Editor Regarding the Article: “Inappropriate Prescribing to Elderly Patients in an Internal Medicine Ward” - Pedro Augusto Simões; Luiz Miguel Santiago; José Augusto Simões (Acta Médica Portuguesa, 2019)
N/a.